2016
DOI: 10.3906/tar-1502-46
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of used engine oil in a wastewater sludge-amended agricultural soil

Abstract: Soil contamination by used engine oil is a common occurrence in most developing countries. This has been shown to have harmful effects on the environment and human beings at large. Used oils are considered to be hazardous waste materials. These are composed of toxic chemicals, such as heavy metals (which come from additives and wear and tear of engine parts), combustion products, light hydrocarbons, polar compounds, uninuclear and polynuclear aromatic compounds, resinous materials, and organometallic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Biostimulation is the addition of growth-limiting factors such as substrates, vitamins, oxygen, and modifying the environmental conditions (temperature, moisture, pH, redox potential, terminal electron acceptors, etc.) in the hydrocarbon-contaminated environments [49,50,52].…”
Section: Biostimulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Biostimulation is the addition of growth-limiting factors such as substrates, vitamins, oxygen, and modifying the environmental conditions (temperature, moisture, pH, redox potential, terminal electron acceptors, etc.) in the hydrocarbon-contaminated environments [49,50,52].…”
Section: Biostimulationmentioning
confidence: 99%
“…When hydrocarbon contaminants are greatly available, they provide high carbon and energy but nitrogen or phosphorus for bacterial growth [31]. Hence, there is the need for the addition of nutrients in hydrocarbon-contaminated sites to increase the required nutrients and stimulate the growth of indigenous bacteria [52]. However, there are certain limitations for effective biostimulation application.…”
Section: Biostimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cadmium and lead are more perilous because they tend to bioaccumulate [6]. According to Dindar et al [7], a high bioremediation rate was observed when waste water sludge containing heavy metals; zinc, copper, nickel, lead and cadmium was used as a biostimulating agent in the bioremediation of engine oil contaminated soil. Therefore, the aim of the study was to investigate the effects of cadmium and lead on biodegradation of diesel in soil.…”
Section: Introductionmentioning
confidence: 99%